(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the clinical characteristics and sleep disturbances in patients with herpes zoster-related pain. Subjects and methods: Cross-sectional descriptive study with analytical components was conducted on 140 patients presenting to Can Tho city Dermatology Hospital between 6/2025 and 2/2026. Results: The mean age was 59.79 ± 12.76. Females accounted for higher proportion than males, at 58.6% and 41.4%, respectively. Among systemic symptoms, fatigue was the most common manifestation (71.4%), followed by fever (52.1%) and headache (36.4%). Herpes zoster lesions were predominantly located on the right side of body (52.1%), faccounted fory the left side (40.7%), while bilateral involvement accounted 7.2%. Most patients had moderate disease severity (49.3%), whereas mild and severe disease accounted for 40% and 10.7%, respectively. The mean age in the sleep disturbance group was significantly higher than that in non-sleep disturbance group (61.12 ± 12.08 vs. 56.84 ± 13.41 years, p < 0.05). The prevalence of sleep disturbances increased progressively with disease severity, from 46.4% in the mild group to 71% in the moderate group and 93.3% in the severe group (p < 0.05). Conclusion: Sleep disturbances were highly prevalent among patients with herpes zoster-related pain and increased progressively with greater clinical severity.